Brain stem death : a chronicle of three decades of search for its cellular and molecular mechanisms - Chan, Samuel H. H. (Switzerland : Karger, 2022)
Novel clinical biomarker and cellular and molecular mechanisms of brain stem death discovered.
Keywords: MUERTE CEREBRAL; TRONCO CEREBRAL; MARCADORES BIOQUIMICOS